PENGARUH JENIS STEK TERHADAP KEBERHASILAN PEMBIBITAN BAMBU HITAM (Gigantochloa atroviolaceae Widjaja) - Aditya Hani (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2020)
Black bamboo seedlings through vegetative propagation still need to be developed in order to obtain the right propagation technique. Trials of making black bamboo seedlings from branch cuttings resulted in a low success rate. This study aims to determine the type of black bamboo stem cutting material. This study used a completely randomized design method (CRD) with the treatment of cuttings, namely: stem cuttings from the weevil (remaining cut), 1-segment stem cuttings, 2-segment stem cuttings, 3-segment stem cuttings. The parameters observed were shoot height, diameter, number of shoot and root length. The result show that the treatment of weevil stem cuttings produced the best shoot growth in all growth parameters.